Mevlana Jelaleddin Rumi’s eternal philosophy - Kayadibi, Saim (IIUM Press, 2011)
To give absolute attention to only external aspects of the thoughts world of Mevlâna will not open wisdom to understand him. However without his inner dimensions are not comprehended, the accurate side of Rûmi will never be materialized by people. In this respect, harmonizing the both dimensions and discovering the relationship of fıqh-ı zâhir (outer meaning) and fıqh-ı bâtın (inner meaning) in the scope of Sufism which elevated Mevlâna Jelâleddin Rûmi to a highly exceptional position. Rûmi’s attentiveness on both meanings, inner and outer, altogether in his works made the human beings to give extra attention to him. Deep comprehension of Mevlâna’s philosophy that was attracted by all mankind especially by the Westerners because of instilling his thoughts in the most enthusiastic matter of intellect-human, death and love-God which he has developed within extraordinary meanings that conveyed Rûmi to the heart of the world. This paper will try to evaluate the spiritual position of Mevlâna’s philosophy among the people of intellect and wisdom as well as to delve deeper in his mystic aspects that conveyed him to the universal dimension.